The boundaries of discretionary power in tax law – contemporary jurisprudence and court rulings (Discourse of Law and Administration, 2023)
Certain tax-law institutions comprise the authority to act within the scope of discretionarypower. The extent of such discretion on the part of administrative authorities is limited by thenotion of boundaries of discretion. Such boundaries lack a legal definition. Their grounds and natureare subject to discovery by the jurisprudence and administrative courts’ case law. Attention is drawnin the present paper specifically to the constitutional principles, rules of tax procedure and directivesfor selection of legal consequences.
Keywords: discretionary power; boundaries of discretionary power; application of tax law; grounds for boundaries of discretion